Living donor uterus transplant research project in Singapore: Progress of the first case - Hak Koon Tan; Terence Y. S. Kee; Bien Keem Tan; Pernilla Dahm‐Kähler; Niclas Kvarnström; Ravinchandran Nadarajah; Khong Yik Chew; Ban Hock Tan; Tew Hong Ho; Lay Kok Tan; Yin Ru Tan; Sobhana Thangaraju; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction To report the progress of the human living uterus transplant research project in Singapore. Material and Methods The uterus transplant research project began in 2012 with a collaboration between the Swedish and Singapore teams. Ethics approval was obtained from the SingHealth Centralised Institutional Review Board, the SingHealth Transplant and the Singapore General Hospital Biomedical Ethics Committee to perform 5 uterus transplant procedures in a collaborative multi‐site research study at the Singapore General Hospital. Regulatory approval was obtained from the Ministry of Health, Singapore. A suitable recipient–donor pair was identified. The living donor was the perimenopausal mother‐in‐law of the recipient who had Mayer–Rokitansky–Kuster–Hauser syndrome. They underwent the requisite matching process as well as robust medical, psychiatric and psychosocial assessments. The recipient then underwent in vitro fertilization (IVF) treatment resulting in 6 frozen blastocysts. Preparations were made for the transplant surgery on 25 November 2023 in Singapore General Hospital, aided by the 3 Uterus transplant experts from the Swedish Team, for whom temporary registration was granted by the Singapore Medical Council. Results This first uterus transplant procedure involved an operative time of 10 h and 30 min for the donor. The synchronized recipient surgery lasted 6 h and 20 min. Surgery was by midline laparotomy in both the living donor and recipient. The total warm ischemic time of the graft was 45 min, and the cold ischemic time was 1 h 45 min (total ischemic time 2 h 30 min). The patient's first menstruation occurred 38 days after the uterus transplant procedure. Cytomegalovirus infection was detected 6 weeks postoperatively for which she was aggressively treated. Serial cervical biopsies showed no rejection and Doppler ultrasound of the transplanted uterus showed good uterine blood flow. Conclusions To date the Living Donor Uterus Transplant Research Project in Singapore has progressed with a uterus transplant surgery involving a living donor performed by a multidisciplinary team. The recipient had a menstrual period 38 days postoperatively. Further study of the outcomes from this procedure will inform the safety and efficacy of uterus transplant in the Singapore context.